2018
DOI: 10.1002/ange.201805019
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic Enantioselective Cross‐Vinylogous Rauhut–Currier Reaction of Methyl Coumalate with Enals

Abstract: The organocatalytic enantioselective intermolecular cross‐vinylogous Rauhut–Currier (RC) reaction of methyl coumalate with α,β‐unsaturated aldehydes is reported, and the enals are activated by iminium catalysis to serve as the Michael acceptors and methyl coumalate is used as an activated diene to generate a latent enolate. The excellent selectivity is driven by the aromaticity of methyl coumalate, and the post transformation of this heterocyclic structure into other electron‐deficient arenes and heterocycles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Finally, it is worth mentioning the direct, organocatalytic, enantioselective intermolecular cross- vinylogous Rauhut–Currier reaction of methyl coumalate 717 and α,β-unsaturated aldehydes 718 recently developed by Liu and Zu, in which the enals were activated via iminium ion catalysis to serve as the Michael acceptors and methyl coumalate was used as an activated diene to generate the latent enolate ( Scheme 184 ). 484 Indeed, prolinol silylether A13 in the presence of 2-trifluoromethylbenzoic acid ( 720 ) as cocatalyst promoted the conjugate addition of pronucleophilic ester 717 to a varied repertoire of aromatic and aliphatic enals 718 to provide enantioenriched products 719 in high yields (up to 99%) and enantioselectivity (up to 99%). Several alternative pathways were proposed with a common pattern: a first nucleophilic, conjugate addition of EtOH or the prolinol to the C6 of methyl coumalate 717 would generate a transient dienolate 717′ , which could trigger the subsequent intermolecular 1,4-addition to the chiral, α,β-unsaturated iminium ion 718′ .…”
Section: Vinylogous Esters and Lactonesmentioning
confidence: 99%
“…Finally, it is worth mentioning the direct, organocatalytic, enantioselective intermolecular cross- vinylogous Rauhut–Currier reaction of methyl coumalate 717 and α,β-unsaturated aldehydes 718 recently developed by Liu and Zu, in which the enals were activated via iminium ion catalysis to serve as the Michael acceptors and methyl coumalate was used as an activated diene to generate the latent enolate ( Scheme 184 ). 484 Indeed, prolinol silylether A13 in the presence of 2-trifluoromethylbenzoic acid ( 720 ) as cocatalyst promoted the conjugate addition of pronucleophilic ester 717 to a varied repertoire of aromatic and aliphatic enals 718 to provide enantioenriched products 719 in high yields (up to 99%) and enantioselectivity (up to 99%). Several alternative pathways were proposed with a common pattern: a first nucleophilic, conjugate addition of EtOH or the prolinol to the C6 of methyl coumalate 717 would generate a transient dienolate 717′ , which could trigger the subsequent intermolecular 1,4-addition to the chiral, α,β-unsaturated iminium ion 718′ .…”
Section: Vinylogous Esters and Lactonesmentioning
confidence: 99%
“…[125] et al reported an organocatalyzed enantioselective Rauhut-Currier reaction of methyl coumalate (191) with α,β-unsaturated aldehydes 313. [128] The enals 313 were activated by iminium catalysis to serve as Michael-acceptors, while 1,6-addition of a nucleophile to pyrone 191 generated the latent enolate. The latter is also facilitated by the activation of pyrone 191 by the organocatalyst 314.…”
Section: Conjugate Additionmentioning
confidence: 99%
“…Enantioselective Rauhut-Currier reaction of methyl coumalate (191). [128] Scheme 64. Morita-Baylis-Hillman reaction of methyl coumalate (191).…”
Section: Cross-coupling Reactionsmentioning
confidence: 99%
“…In addition, reactions with soft nucleophiles such as β‐ketoesters, 1,3‐diketones, or amines allow access to 2H ‐pyrans, [28] aromatic compounds, [29] and pyridines, [30–31] respectively. To the best of our knowledge, the involvement of methyl coumalate in a cross‐vinylogous Rauhut‐Currier reaction [32] and in a Morita‐Baylis‐Hillman reaction [33] are the scarce examples of processes giving access to coumalate adducts. Surprisingly, there is no report of carbon‐carbon bond formation from methyl 3‐bromo coumalate (3‐BrMC) and an organometallic species under transition metal catalysis, whereas brominated, triflyloxy‐ or tosyloxy‐pyran‐2‐ones readily react under Sonogashira, [34] Negishi, [5] Suzuki, [35–38] Stille [39–42]− type couplings or with Me 3 Al−dimethylaminoethanol complex as coupling reagent [43] .…”
Section: Introductionmentioning
confidence: 99%